2015
DOI: 10.1007/s00784-015-1436-1
|View full text |Cite
|
Sign up to set email alerts
|

Fluoride dose-response of human and bovine enamel artificial caries lesions under pH-cycling conditions

Abstract: Objectives This laboratory study aimed to: a) compare the fluoride dose-response of different caries lesions created in human and bovine enamel (HE/BE) under pH-cycling conditions, and b) investigate the suitability of Knoop and Vickers surface microhardness (K-SMH/V-SMH) in comparison to transverse microradiography (TMR) to investigate lesion de-and remineralization.Materials and Methods Caries lesions were formed using three different protocols (Carbopol, hydroxyethylcellulose-HEC, methylcellulose-MeC) and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 29 publications
1
44
1
Order By: Relevance
“…Moreover, this invitro study used not human enamel teeth but bovine enamel teeth. Bovine enamel teeth were more easily demineralized than human enamel teeth 20) . Therefore, further studies need to adopt a clinical trial design and in-vitro study using human enamel teeth.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, this invitro study used not human enamel teeth but bovine enamel teeth. Bovine enamel teeth were more easily demineralized than human enamel teeth 20) . Therefore, further studies need to adopt a clinical trial design and in-vitro study using human enamel teeth.…”
Section: Discussionmentioning
confidence: 91%
“…Evidently, the amount of fluoride release means remineralization because the amount of fluoride release is directly proportional to the amount of remineralization 20) . However, some research suggested that remineralization did not depend on the amount of fluoride release 21) .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the effects are higher when fluoride-or calcium-based compounds are irradiated concurrently [11][12][13][14]17]. Nevertheless, the data show that the mineral content of the laser group was similar to the control.…”
Section: Discussionmentioning
confidence: 99%
“…Bovine enamel was used as a model for human teeth. This model offers a large surface area and more uniform enamel thickness; previous studies have shown that they are very similar to human teeth [15][16][17].…”
Section: Introductionmentioning
confidence: 95%
“…The key of remineralization or regeneration of tooth hard tissue is finding an appropriate organic template and inducing the process of mineralization. The frequently used agents are fluoride [3], salivary proteins [4], casein phosphopeptide amorphous calcium phosphate [5], or organic polymers [6]. However, these approaches either call for too severe conditions to apply in clinics, or reconstruct structures unlike natural enamel.…”
Section: Introductionmentioning
confidence: 99%